Discharge in bankruptcy: a comparative analysis of law and practice between Malaysia, Singapore and the United Kingdom (UK) – What can we learn? - Azmi, Ruzita (Taylor & Francis Group, 2017)
In common law jurisdictions such as Malaysia, United Kingdom and Singapore, bankruptcy law is the legal mechanism in situations where individuals fall into bankruptcy. In the UK, automatic discharge was introduced fifteen years ago. Yet, no equivalent concept of automatic discharge has been introduced in Singapore, while in Malaysia, although a new provision allowing for an automatic discharge of bankrupt was proposed in the new Bankruptcy (Amendment) Bill 2016, it has yet to come into force upon official announcement by the Malaysian authorities. This paper examines and compares the laws and practices of discharge of bankrupts in Malaysia, the UK and Singapore.